2002
DOI: 10.1086/338415
|View full text |Cite
|
Sign up to set email alerts
|

Damping of Terrestrial‐Planet Eccentricities by Density‐Wave Interactions with a Remnant Gas Disk

Abstract: We examine the damping of terrestrial-planet eccentricities via density-wave interactions with a remnant gas disk that postdated the accretionary epoch. A lower limit is estimated for the gas surface density present in the terrestrial zone required for acoustic damping to be e †ective, and a simple model for describing the diskÏs inÑuence on the planet eccentricities is presented. The results suggest that the terrestrial-planet eccentricities could be reduced from values permitting crossing orbits to the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…It is also interesting that both planets damp at the same rate, even though their individual torques and angular momenta are unequal. Again, this is due to communication between the planetary pair via their mutual torque (e.g., Agnor & Ward 2002). Using the same semimajor axes as before, g( 1 3 ) = 0.51, (sin I s ) À1 dI s /dt % 0.097l d 2 , and damp $ 140l À1 d yr. For this example, the external resonance lies at a distance r r $ (a 2 /a 1 ) 3/7 a 2 /f f = 1.6a 2 = 24 AU, in pretty good agreement with the $25 AU value of Figure 2. …”
mentioning
confidence: 91%
“…It is also interesting that both planets damp at the same rate, even though their individual torques and angular momenta are unequal. Again, this is due to communication between the planetary pair via their mutual torque (e.g., Agnor & Ward 2002). Using the same semimajor axes as before, g( 1 3 ) = 0.51, (sin I s ) À1 dI s /dt % 0.097l d 2 , and damp $ 140l À1 d yr. For this example, the external resonance lies at a distance r r $ (a 2 /a 1 ) 3/7 a 2 /f f = 1.6a 2 = 24 AU, in pretty good agreement with the $25 AU value of Figure 2. …”
mentioning
confidence: 91%
“…If the timescale is long, the velocity dispersion of planetesimals is suppressed by the gas drag. Hence, the gravitational focusing effect of protoplanets is enhanced, resulting in a fast cleanup of remnant planetesimals and a lower eccentricity distribution of the final planets (Agnor & Ward 2002;Kominami & Ida 2002, 2004Nagasawa et al 2005;Ogihara et al 2007). On the other hand, if the timescale of gas dissipation is short, planetesimals remain unaccreted by protoplanets for a longer period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Kominami & Ida (2002 performed N-body simulations, taking into account the eccentricity damping caused by tidal interaction with a remnant gas disk and found that final eccentricities can be small enough to be consistent with those of Earth and Venus. The remnant disk with Σ g = 10 −4 -10 −3 Σ g,MMSN allows orbit crossing, but it is still enough to damp eccentricities of Earth-mass planets to 0.01 within disk depletion timescale ∼ 10 6 -10 7 years (Kominami & Ida 2002;Agnor & Ward 2002). …”
Section: Introductionmentioning
confidence: 99%